1986
DOI: 10.1002/j.1460-2075.1986.tb04213.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a provirally activated c-Ha-ras oncogene in an avian nephroblastoma via a novel procedure: cDNA cloning of a chimaeric viral-host transcript.

Abstract: Retroviruses without oncogenes often exert their neoplastic potential as insertional mutagens of cellular proto-oncogenes.This may be associated with the production of chimaeric viral -host transcripts; in these cases, activated cellular genes can be identified by obtainig cDNA clones of bipartite RNAs. This approach was used in the analysis of chicken nephroblastomas induced by myeloblastosis-associated virus (MAV). One tumor contained a novel mRNA species initiated within a MAV LTR. cDNA cloning revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 84 publications
1
34
0
2
Order By: Relevance
“…Since these pathways are constituted by cascades of functionally connected genes, the provirus does not have to hit one particular gene in order to deregulate the pathway. That is probably why the efforts to identify the crucial nephroblastoma-specific integrations had only a limited success (Westaway et al, 1986;Joliot et al, 1992). That is also probably why nephroblastomas display histopathological variations, since distinct deregulated genes have a different impact on the phenotype of transformed cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these pathways are constituted by cascades of functionally connected genes, the provirus does not have to hit one particular gene in order to deregulate the pathway. That is probably why the efforts to identify the crucial nephroblastoma-specific integrations had only a limited success (Westaway et al, 1986;Joliot et al, 1992). That is also probably why nephroblastomas display histopathological variations, since distinct deregulated genes have a different impact on the phenotype of transformed cells.…”
Section: Discussionmentioning
confidence: 99%
“…c-Ha-ras and c-fos proto-oncogenes have also been found to be activated by the retrovirus in chicken nephroblastoma. However, their role seems to be limited to single cases (Westaway et al, 1986;Collart et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of activated Ras in melanocytes null for p16 induces melanoma tumors (Chin et al, 1999) and overexpression of mutant activated M-Ras induces transforming foci in NIH3T3 cells, although the ability of M-Ras to induce transforming foci is weaker than that of Ha-Ras (Quilliam et al, 1999). It has been reported that over-expression of any of three normal Ras genes, N-Ras (McKay et al, 1986), H-Ras (Westaway et al, 1986;Zhang et al, 1997) or K-Ras (George et al, 1986) leads to in vitro transformation. In vivo, overexpression of normal N-Ras is associated with development of hyperplasia and tumors in transgenic mice (Mangues et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Ras activation mutations frequently result from single point mutations at amino acid 12 or 61 (Capon et al, 1983) with the most frequent involving a point mutation at codon 12 of Ki-ras. In addition, perturbation of ras signaling in cancer does not only occur through ras activation by point mutations, but is also associated with abnormally high levels of Ras proteins, which may result from gene ampli®cation (Filmus and Buick, 1985;Bos et al, 1986;Fuijita et al, 1985;Graham et al, 1985), or from dysregulated expression (George et al, 1986;Westaway et al, 1986).…”
Section: Introductionmentioning
confidence: 99%